ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMP - Utami, Rina Indriyani; Setiawan, Wahyu; Yuliani, Anik (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was to determine the difficulties experienced by students in solving story problems in teaching materials for the Two Variable Linear Equation System (SPLDV) in secondary schools. The system of linear equations of two variables, or often called SPLDVs, is one of the most familiar materials in everyday life. The survey was also conducted in a secondary school in West Bandung Province with a total of 27 class VIII B students. A sample of 10 individuals was taken for further analysis to represent students with high, medium and low abilities. Qualitative descriptive method was also used in this study. Data collection itself is done through student test sheets containing two story questions with different levels of difficulty. The test results showed that (1) the students did not understand the story questions, and (2) the students were not comfortable in modifying and modeling the story questions. (3) retraining is needed because they are not familiar with converting values to mathematical models using the substitution method.Â